Gender Inequality and Women Participation in Politics: A Case Study of Jibia Local Government Area - Dalha, Abdurrashid (Kashere Journal of Politics and International Relations, 2023)
Political stability and development of any political system is a function of the awareness and inclusive involvement of the citizens in its political activities irrespective of gender. Thus, poor participation of women in politics and governance has been a major concern at global level. Low level participation of Nigerian women in politics is often associated with culture, religious and economic constraint. The study, therefore; aims at examining the causes and effects of poor political participation of women as well as identifying the relationship between gender inequality and women inactive political participation in Jibia Local Government during the Fourth Republic. The study applies theories of sexism and gender perspective to illustrate causes and effects of women underrepresentation in Nigerian politics. A survey method was adopted with 150 people selected using accidental sampling technique to serve as respondents and SPSS vasion 25 was used in data analysis. The findings of the research show that child bearing and nurturing, religious practices and the role assign to women by the society are the major factors that cause poor political participation among women which affect the quality of democracy in the country. It is, therefore; recommended that discriminatory socio-cultural and religious practices against women active participation in politics in Nigeria should be positively reviewed by stakeholders (particularly traditional/religious rulers) who should be educated to be gender sensitive and encouraged to protect women political and other rights and ensure support of their political and any important meeting of the family, Community and even in government establishments.